Mutually exclusive capital projects: A critique of Fisherian analysis - S. Paulo (South African Journal of Business Management, 1994)
In capital budgeting a Fisherian analysis is undertaken to resolve conflicts in rankings which arise when mutually exclusive projects have been evaluated according to the net present value and internal rate of return criteria. Within the literature, the projects which have been subjected to a Fisherian analysis, all have the same required rates of return because the required rate of return is held constant irrespective of the differences in the characteristics of the mutually exclusive projects. The conflict in rankings of mutually exclusive projects is typically ascribed to characteristics such as differences in initial outlay and project life span, disparities in the timing of cash flows, the reinvestment rate assumption, and the difficulties of multiple or no unique internal rate of return when the cash flows are non-conventional. Despite these differences among projects, the same required rate of return is used. The central question which is addressed in this article, is whether the same required rate of return can reasonably be used for the valuation of each of the mutually exclusive projects, as well as when a choice is made from among the mutually exclusive projects. In the discussion this 'conventional wisdom' of a constant required rate of return for both the valuations and the choice of an alternative is questioned, and it is suggested that one of the causes of a conflict in rankings may be the use of incorrectly specified required rates of return. Also presented in this article is a conceptual framework which enables a modified Fisherian analysis.
Keywords: 650